Evaluating the potential of underwater television to contribute to marine litter assessments alongside bottom trawling - Katja Norén; Filip Svensson; Max Lindmark (PLoS ONE, 2025)
Marine litter presents a global threat to marine ecosystems, human health, and safety. Therefore, it is important to increase our knowledge about spatiotemporal trends of litter in the environment. Bottom trawl surveys provide a practical method for monitoring seafloor litter on the continental shelf, but can have severe negative impacts on the environment. Here we evaluate the potential of an ongoing underwater television survey (UWTV) to also collect litter density data, and develop model-based indices of litter densities integrating coastal and offshore trawl survey data using geostatistical models. Based on our case study along the Swedish west coast, we find that UWTV in its current format may be limited as an alternative to trawling in areas with relatively low densities. There are also clear spatial trends in litter, with the highest densities in near-shores areas currently only included in the national monitoring program. Our results illustrate the potential of combining data, but also the importance of careful sampling designing for marine litter monitoring.